A wake‐up call to quiescent cancer cells – potential use of DYRK1B inhibitors in cancer therapy. (12th December 2017) - Becker, Walter
Abstract : Nondividing cancer cells are relatively resistant to chemotherapeutic drugs and environmental stress factors. Promoting cell cycle re‐entry of quiescent cancer cells is a potential strategy to enhance the cytotoxicity of agents that target cycling cells. It is therefore important to elucidate the mechanisms by which these cells are maintained in the quiescent state. The protein kinase dual specificity tyrosine phosphorylation‐regulated kinase 1B (DYRK1B) is overexpressed in a subset of cancers and maintains cellular quiescence by counteracting G 0 / G 1 –S phase transition. Specifically, DYRK1B controls the S phase checkpoint by stabilizing the cyclin‐dependent kinase (CDK) inhibitor p27 Kip1 and inducing the degradation of cyclin D. DYRK1B also stabilizes the DREAM complex that represses cell cycle gene expression in G 0 arrested cells. In addition, DYRK1B enhances cell survival by upregulating antioxidant gene expression and reducing intracellular levels of reactive oxygen species (ROS). Substantial evidence indicates that depletion or inhibition of DYRK1B drives cell cycle re‐entry and enhances apoptosis of those quiescent cancer cells with high expression of DYRK1B. Furthermore, small molecule DYRK1B inhibitors sensitize cells to the cytotoxic effects of anticancer drugs that target proliferating cells. These encouraging findings justify continued efforts to investigate the use of DYRK1B inhibitors to disrupt the quiescent state and overturn chemoresistance of noncycling cancer cells. Abstract : Quiescent cancer cells can resist environmental stress and anticancer therapy. The protein kinase dual specificity tyrosine phosphorylation‐regulated kinase 1B (DYRK1B) inhibits S‐phase entry and supports cancer cell survival by upregulation of antioxidant gene expression. The present review summarizes evidence that pharmacological inhibition of DYRK1B can purge DYRK1B‐overexpressing cancer cells from quiescence and sensitize cells to the cytotoxic effects of anticancer drugs.